Developing a Sustainable Technology-Integrated Professional Development Model for Arabic Language Teachers in Madrasah - Khosip Ikhsan; Khoirul Faizin (Attanwir : Jurnal Keislaman dan Pendidikan, 2026)
This study addresses the increasing demand for meaningful technology integration in education, which has not yet been adequately supported by systematic and sustainable professional development models, particularly in Arabic language teaching in madrasah. The study aims to develop a sustainable, reflective, and contextually grounded professional development model based on technology integration. This research employed a Research and Development (R&D) approach using a Design-Based Research (DBR) framework involving 30 Arabic language teachers at the Madrasah Aliyah level. Data were collected through questionnaires, interviews, observations, and document analysis, and analyzed using descriptive statistics and thematic analysis. The findings reveal a high level of need for sustainable technology-based professional development. The developed model (Pro-TArMad) was validated as highly valid by experts and demonstrated effectiveness through iterative DBR cycles, as indicated by improvements in teachers’ TPACK competence and instructional practices. The model emphasizes continuous cycles of needs analysis, design, implementation, reflection, and refinement. This study contributes both practically, by offering an implementable model for madrasah, and theoretically, by advancing the discourse on sustainable teacher professional development in technology-enhanced language education.